Burden of illness in systemic lupus erythematosus: results from a UK patient and carer online survey. (September 2017) - Kent, T; Davidson, A; Newman, D; Buck, G; D'Cruz, D
Objective: The objective of this study was to assess the impact of systemic lupus erythematosus (SLE) on patients and carers. Methods: Adults with SLE and carers of SLE patients completed a UK-specific online survey covering many aspects of the disease. Surveys were developed in collaboration with an NHS lupus unit and a lupus patient organization. Results: A total of 121 patients and 31 carers completed the surveys. Of the 70% of patients initially misdiagnosed with another condition, 59% received treatment for the misdiagnosis. Fatigue was the most debilitating symptom, experienced daily by 79% of patients. The proportion of patients not reporting flares to healthcare providers varied with flare severity: mild flares (43%), moderate flares (15%) and severe flares (5%). Most patients (89%) reported reduced ability to socialize, and 76% had changed employment; of these, 52% stopped working completely. Over one-half (52%) of carers in paid employment missed time from work, and 55% of carers reported a worsened financial status. Most carers (87%) experienced interference with social activities. Conclusion: SLE is commonly misdiagnosed and has a considerable impact on the physical, social and financial status of patients and carers. Increased awareness of the disease among healthcare providers and employers of patients and their carers is needed.